Hard magnetic property of Mn-Ga-Al melt-spun ribbons - Thanh, Pham Thi; Lam, Nguyen Mau; Oanh, Dinh Thi Kim; Ngoc, Nguyen Huy; Hau, Kieu Xuan; Yen, Nguyen Hai; Anh, Truong Viet; Quang, Vu Manh; Nga, Nguyen Thi Nguyet; Dan, Nguyen Huy (Vietnam Journal of Science and Technology, 2022)
. Mn-Ga-based alloy system has exhibited hard magnetic properties, although this alloy system contains no rare earth elements. However, magnetic parameters of Mn-Ga alloys have not yet been comparable to those of rare earth magnets such as Nd-Fe-B, Sm-Co, etc. Therefore, enhancement of the magnetic properties of the Mn-Ga-based alloys has interestingly been researched by scientists in the world. Partial replacement of both the Ga and Mn by other elements (Al, Cu, Bi, Cr, etc.) with suitable synthesis conditions (annealing temperature, annealing time, etc.) have shown improvement in the magnetic properties of the Mn-Ga-based alloys. In this paper, we investigated the effect of Al concentration and annealing conditions on the structure and magnetic properties of Mn65Ga25-xAl10+x (x = 0, 5 and 10) alloy ribbons prepared by melt-spinning method. Crystalline phases of MnAl, D019-type Mn3Ga and D022-type Mn3Ga were found in all the ribbons. The D022-type Mn3Ga hard magnetic phase is dominated by appropriate Al concentration and annealing conditions. Coercivities, Hc, greater than 10 kOe were achieved on the alloys at an optimal annealing temperature and time of 650 oC and 1 h, respectively. The obtained results show applicability of the Mn-Ga-based alloys as a new kind of rare earth-free hard magnetic materials in applications.